CAD/CAM of industrial product / Abdul Rahman Yusof and Rasli Mohamad - Yusof, Abdul Rahman; Mohamad, Rasli (1996)
The Computer Aided Design and the Computer Aided Manufacturing CAD/CAM programming is the creation and manipulation of model or prototypes on a computer to assist in the design process. The purpose of this design process, analyzing and practical are to study on the CAD/CAM programming and machining process using the Computer Numerical Control (CNC) machine. The design of a product by CAD modelling is a popular process nowadays. The process of modelling does not only makes producing easier but also it saves time and cost involved in the long-run. The product can be standardized and its quality preserved as long as the modelling used is not defect in any way. Computer Aided Design (CAD) is a system which enables the user to create any shape they desire with the aid of a computer. With the modernized technology, the CAD system does not only makes the process of creating easier but its application is now in a growing process. The reason is to enable the system to communicate with other external system such as CNC machines so that it can interpret creating and designing information that has been done before.